ANALISIS YURIDIS KEDUDUKAN BADAN PENGAWAS PASAR MODAL (BAPEPAM) SETELAH BERLAKUNYA UNDANG-UNDANG NO. 21 TAHUN 2011 TENTANG OTORITAS JASA KEUANGAN - Susi Muliyanti; Sunarmi Sunarmi; Mahmul Siregar; Utary Maharany Barus (USU LAW JOURNAL, 2013)
The roles of Capital Market Supervisory Agency (Badan Pengawas Pasar Modal – Bapepam) are to guide, rule and supervise capital market. The issuance of Law on Financial Service Authority takes over the authorities of the Capital Market Supervisory. The establishment of Financial Service Authority is mandated by Article 34 of Law on Bank Indonesia as an independent institution which regulates and supervises all financial service sectors by applying an unified supervisory model which separates the regulating and supervising tasks. Prior to the issuance of Law on Financial Service Authority, financial service sectors in capital market are supervised by Capital Market Supervisory Agency which is structurally still under the coordination of Ministry of Finance so that its authorities are still limited and result in the high number of cases of capital market which cannot be addressed effectively. Since Capital Market Supervisory Agency needs to be independent, it prefers to transform and merge into Financial Service Authority. It is suggested that laws related to banking, capital market, the Deposit Insurance Agency (Lembaga Penjamin Simpanan – LPS) need to be harmonized to prevent overlapping in their authorities. Therefore, Draft Bill on UUPM needs to be passed immediately because Capital Market Supervisory Agency has emerged into Financial Service Authority while UUPM still regulates the authorities of Capital Market Supervisory Agency. Financial Service Authority has to make regulations related to investigative authorities to address cases of capital market properly.